PRINCIPLES OF DEVELOPMENT OF THE SYSTEM OF MAINTENANCE AND REPAIR OF TERMINAL FACILITIES OF AIR TRAFFIC CONTROL - A. V. Prokhorov; D. S. Bondar’ (Научный вестник МГТУ ГА, 2016)
This article describes the questions connected with development of the system of maintenance and repair of terminal facilities of air traffic control.